A recurrent pathogenic variant in TPM2 reveals further phenotypic and genetic heterogeneity in multiple pterygium syndrome‐related disorders. Issue 6 (4th March 2020) - Vogt, Julie; Al‐Saedi, Atif; Willis, Tracey; Male, Alison; McKie, Arthur; Kiely, Nigel; Maher, Eamonn R.
Abstract: Multiple pterygium syndrome (MPS) disorders are a phenotypically and genetically heterogeneous group of conditions characterized by multiple joint contractures (arthrogryposis), pterygia (joint webbing) and other developmental defects. MPS is most frequently inherited in an autosomal recessive fashion but X‐linked and autosomal dominant forms also occur. Advances in genomic technologies have identified many genetic causes of MPS‐related disorders and genetic diagnosis requires large targeted next generation sequencing gene panels or genome‐wide sequencing approaches. Using the Illumina TruSightOne clinical exome assay, we identified a recurrent heterozygous missense substitution in TPM2 (encoding beta tropomyosin) in three unrelated individuals. This was confirmed to have arisen as a de novo event in the two patients with parental samples. TPM2 mutations have previously been described in association with a variety of dominantly inherited neuromuscular phenotypes including nemaline myopathy, congenital fibre‐type disproportion, distal arthrogryposis and trismus pseudocamptodactyly, and in a patient with autosomal recessive Escobar syndrome and a nemaline myopathy. The three cases reported here had overlapping but variable features. Our findings expand the range of TMP2 ‐related phenotypes and indicate that de novo TMP2 mutations should be considered in isolated cases of MPS‐related conditions. Abstract : A Recurrent Pathogenic Variant in TPM2 Reveals Further Phenotypic and Genetic Heterogeneity in Multiple Pterygium Syndrome‐Related Disorders.